Women and the informal economy in urban Africa From the margins to the centre - Kinyanjui, Mary Njeri (Africa Now, 2014)
In this highly original work, Mary Njeri Kinyanjui explores the trajectory of women's movement from the margins of urbanization into the centres of business activities in Nairobi and its accompanying implications for urban planning.While women in much of Africa have struggled to gain urban citizenship and continue to be weighed down by poor education, low income and confinement to domestic responsibilities due to patriarchic norms, a new form of urban dynamism - partly informed by the informal economy - is now enabling them to manage poverty, create jobs and link to the circuits of capital and labour. Relying on social ties, reciprocity, sharing and collaboration, women's informal 'solidarity entrepreneurialism' is taking them away from the margins of business activity and catapulting them into the centre.Bringing together key issues of gender, economic informality and urban planning in Africa, Kinyanjui demonstrates that women have become a critical factor in the making of a postcolonial city.